223 IMPROVEMENTS IN CAROTID ARTERY INTIMA-MEDIA THICKNESS IN TYPE 2 DIABETIC PATIENTS USING PEROXISOME PROLIFERATOR-ACTIVATED RECEPTOR γ LIGAND, ROSIGLITAZONE. (10th December 2015) - Kronstad, D.; Cole, C.; Aguinaldo, M.; Lyko, A.; Chao, E.; Daud, S.; Krishnamoorthy, S.; Vu, K.; Magbual, R.; Liu, W.; Lee, S.
Abstract : Purpose: Measurement of the carotid artery intima-media thickness (IMT) using high resolution B-mode ultrasonagraphy has emerged as a useful tool for assessing coronary atherosclerosis and cardiac risk. A primary contributor towards coronary atherogenesis in patients with diabetes is endothelial cell dysfunction. The insulin sensitizer and peroxisome proliferator-activated receptor γ (PPARγ) ligand, rosiglitazone (RSG), has been shown to improve endothelial function in preclinical and clinical trials. It has been argued that such improvements may be secondary to corresponding improvements in glucose control over time. We hypothesized that RSG would reduce IMT over a period of 6 months and improve blood vessel health through its positive effect on the endothelium. Methods: RSG 2-4 mg was given daily for 6 months to 15 insulin resistant diabetics (9 male). IMT was measured at baseline and again at 6 months. Each IMT measurement was initiated by the SonoCalc operator at a location in the adventitia of the segment to be measured. Various sonographic interfaces were then initially outlined automatically. If any substantial variance was detected by the operator between the SonoCalc automated IMT border and a border that would have appeared more correct, progressively controlled edit options were employed to achieve satisfactory semi-automatic SonoCalc measurements. The automated and semi-automated SonoCalc software program computed the average thickness of the intima-media complex in each application mode. Results: A trend for improvement in IMT was seen after 6 months. Mean diameter of the intima-media complex at baseline was 0.882 mm while the corresponding measurement at 6 months was 0.862 mm, representing a decrease in 0.02 mm. Although a positive observation, the trend in decreased IMT was not statistically significant (P = 0.198). Conclusions: In conclusion, our preliminary data demonstrates trends in improvements in IMT with RSG in insulin resistant type 2 diabetics after 6 months of therapy. Further evaluation will need to be performed with a larger sample size or a longer duration of study to confirm these results.